DROP SIZE AND DROP SIZE DISTRIBUTION IN A LIQUID-LIQUID EXTRACTION SPRAY COLUMN (Biological Sciences - PJSIR, 2022)
A photographic method was used for the estimation of drop size and drop size distribution obtained from multiplenozzles for a chemical system (zinc/di(2-ethylhexyl) phosphoric acid) for solute transfer from continuous to dispersedand dispersed to continuous phase. The experiments were performed in a glass spray column under semi-batch operation.Experimentally obtained drop sizes were compared with those predicted from drop size correlations for jetting andnon-jetting conditions and the ones predicting best results are given for design purposes.